A bibliometric services workshop for subject librarians. Issue 5 (10th October 2018) - Powell, Kimberly R.; Elder, Jennifer J.
Abstract : Purpose: The purpose of this paper is to report on the development and analysis of an internal bibliometric services workshop for subject librarians. Primary goals of the workshop were to create an opportunity for collegial knowledge and skill sharing, and to identify discipline specific gaps and future support requirements. Design/methodology/approach: Two campus librarians who typically offer bibliometric support services used pre- and post-surveys to plan and assess the workshop for subject liaison librarians. Findings: Subject librarians from across the university expressed interest in developing bibliometric support services. The 12 workshop participants (30 percent of subject librarians) support diverse areas including the humanities, social sciences, life sciences, education and outreach, and the school of business. Post-workshop survey respondents highlighted the contextualization of available measures and the appropriate application of metrics in different disciplines to be the most helpful topics covered. Finally, while the institution subscribes to several citation analysis databases, more familiarity with Google Scholar citations was requested to address user needs and preferences across the various disciplines. Most participants expressed interest in attending additional workshops. Originality/value: This study showcases the experience of campus librarians working together across academic schools and disciplines to respond to the increasing demand for bibliometric and scholarly impact support services. While services such as citation analysis have typically been siloed in specific job descriptions or subject areas within the library, these are service areas that can benefit from internal library-collaboration opportunities and knowledge sharing.